Benzyl butyl phthalate (BBP) induces lung injury and fibrosis through neutrophil extracellular traps. (15th September 2022) - Wang, Weili; Liu, Zhenyu; Zhang, Yu; Wang, Liu; Meng, Dongwei; Li, Xueqin; Zhang, Jingbo; Wu, Yuzhang; Zhou, Xinyuan; Liu, Guoxiang
Abstract: Benzyl butyl phthalate (BBP) is an extensively used plasticizer that has aroused widespread concern about its potential toxicity. Previous evidences demonstrate that BBP exposure is associated with asthma and impaired lung function. Accumulating data indicates that neutrophil extracellular traps (NETs), a particular manner of neutrophil death, play a vital role in the pathogenesis of respiratory diseases. However, the immunotoxicity effects of BBP in lung injury are unclear. Here, we aimed to investigate the potential impacts of BBP-induced NETs on lung injury and fibrosis. Mice treated with BBP exhibited significant lung injury, with alveolar hemorrhage, lung edema and increased neutrophil infiltration. Meanwhile, BBP promoted extensive neutrophil infiltration in bronchoalveolar lavage fluid and NETs deposition in lung tissues. Moreover, BBP clearly triggered NETs formation in vitro, which was confirmed by net-like structures decorated with myeloperoxidase and citrullinated histone H3. Furthermore, BBP fueled glucose uptake and ROS burst of neutrophils playing essential roles during NETs formation. Additionally, we proved that NETs could promote fibrogenesis in murine lung epithelial cells and observed lung fibrosis remarkably after BBP-induced injury. Taken together, our findings indicated that exposure to BBP could increase the risk for lung injury and fibrosis by disturbing innate immunity via NETs formation. Graphical abstract: Image 1 Highlights: BBP exposure induces lung injury and fibrosis. BBP exhibits its immunotoxicity by inducing NETs formation. BBP fuels glucose uptake and ROS burst of neutrophils during NETs formation. NETs promote fibrogenesis of lung epithelial cell.